Experimental Research on the Instantaneous and Long-Term Deflections of Pre-Cracked Concrete Beams Enhanced by Carbon Fibre Reinforced Polymer (Fracture and Structural Integrity, 2018)
This paper aims to disclose the influence law of cracks on instantaneous and long-term deflections of reinforced beam. For this purpose, four concrete beams were created, pre-loaded to varied degrees of cracking, and reinforced with carbon fibre reinforced polymer (CFRP). Then, a 300-day load test was carried out on these samples to measure the instantaneous and long-term deflections. The experimental results show that the pre-cracking degree has little influence on instantaneous deflection; whether a beam is pre-cracked or intact, the final deflection of the beam is mostly affected by its initial deflection before the reinforcement; the pre-cracking degree is negatively correlated to the magnitude of additional deflection under sustained load. The research findings lay the basis for judging whether a reinforced beam can be used normally in the long run.
Keywords: Carbon fibre reinforced polymer (CFRP); Pre-cracked beams; Creep; Long-term deflection